A Research on the Quality of Symbolism in William Butler Yeats’s Poetry: Exploring William Butler Yeats's Symbolic System in Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This examination is an investigation of the development of the symbolic system defined by William Butler Yeats and his ensuing utilization of this system to his poetry, with extraordinary thoughtfulness regarding the rose and the stone. To fathom and in this way completely value Yeats' poetry requires some learning of the powers cooperating to shape the premise of his reasoning and symbolic system. The impact of the French Symbolist Movement on Yeats has frequently been commented upon by the researchers. He is generally clubbed with alternate symbolists like Dylan Thomas, Wallace Stevens, Ezra Pound and others. Nonetheless, very few have dove upon the distinction between the symbolism of Yeats and that of other contemporary present day poets. For writers like T.S. Eliot and Ezra Pound, symbols were a piece of their cutting edge venture which tried to search for more up to date approaches to convey what needs be. Be that as it may, for Yeats, there was no contrast between his perspective and the system of symbols he worked for the duration of his life. This paper investigates the one of a kind and private distraction of Yeats with the coherent system of symbols utilized as a part of his poetry. It additionally looks to follow the development of Yeats' symbolism, the different impacts which molded his manner of thinking and probably the most usually utilized symbols in his poetry.